The eleventh plague - Hirsch, Jeff (Scholastic Press, 2011)
Twenty years after the start of the war that caused the Collapse, fifteen-year-old Stephen, his father, and grandfather travel post-Collapse America scavenging, but when his grandfather dies and his father decides to risk everything to save the lives of two strangers, Stephen's life is turned upside down.